"How am I supposed to do this on my own?": A case study on perspectives of preschool teachers regarding integrative STEM practices. (March 2022) - Demircan, Hasibe Özlen
This article analyzes the perspectives of three preschool teachers on integrative STEM practices and the facilitating and hindering factors in their implementation. The participants were preschool teachers working at public preschools. They volunteered to participate in a 14-hour STEM professional development program and to share their perspectives on the implementation of integrative STEM practice. Here a case-study method is used to conduct an in-depth investigation. Data was collected from teachers through interviews, informal classroom observations, and document analysis. The factors facilitating or hindering the teachers' implementation of integrative STEM practice were analyzed in three aspects: curriculum, pedagogy, learning environment, and the needs they observed while implementing these practices identified. The findings revealed that though the practices are developmentally appropriate to support active learning and time-effectiveness, teachers find it challenging to integrate STEM into education by their own efforts alone. Daily routines, differences between individual children, and material and storage issues are major hindering factors they faced while implementing integrative STEM practices. According to findings, teachers need the support of administration, parents, and colleagues to implement integrative STEM practices. In the short term and the long term, to see a positive impact of integrative STEM practices, there is a need for a better quality context in the curriculum, pedagogy, and learning environment.